2001
DOI: 10.1021/la000554f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulation of a Dichain Surfactant/Water/Carbon Dioxide System. 1. Structural Properties of Aggregates

Abstract: Molecular dynamics simulation of a dichain surfactant + water + carbon dioxide (solvent) system is performed to study the structural properties of reversed micelle-like surfactant aggregates formed in the system. The simulations use a detailed and realistic molecular model for the surfactant molecule and explicit representation of the water and solvent molecules to enable quantitative comparisons with a prior experimental (small-angle neutron scattering) study. The results of the simulation are found to be in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 46 publications
(61 reference statements)
5
120
0
Order By: Relevance
“…X-ray diffraction experiments have been carried out by Kanakubo et al 49 to examine the intermolecular structure of the solution and, in particular, the location and orientation of the CO 2 molecule with reference to the anion. Based on the analysis of experimental data, they have concluded that the CO 2 molecule may not be tangential to the PF 6 sphere as claimed in the computer simulation studies. 46,48,53 We have recently carried out ab initio MD simulations of the [bmim][PF 6 ] -CO 2 mixture at a CO 2 concentration of 70 mol % to study the intermolecular environment around CO 2 molecules in the solution.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…X-ray diffraction experiments have been carried out by Kanakubo et al 49 to examine the intermolecular structure of the solution and, in particular, the location and orientation of the CO 2 molecule with reference to the anion. Based on the analysis of experimental data, they have concluded that the CO 2 molecule may not be tangential to the PF 6 sphere as claimed in the computer simulation studies. 46,48,53 We have recently carried out ab initio MD simulations of the [bmim][PF 6 ] -CO 2 mixture at a CO 2 concentration of 70 mol % to study the intermolecular environment around CO 2 molecules in the solution.…”
Section: Introductionmentioning
confidence: 87%
“…53 It also predicts the diffusion coefficients of ions, density, and surface tension in excellent agreement with experimental data. For the CO 2 molecules, the EPM2 model 56 6 ] were simulated. The systems were first equilibrated under constant temperature and pressure (NPT) conditions, and later in the canonical (NVT) ensemble, with the volume determined as an average over the earlier NPT trajectory.…”
Section: Methodology and Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insight into the microstructure of the bare and surfactant modified C|W interfacial region was recently reported (da Rocha, et al, 2001, Salaniwal, et al, 2001, Senapati, et al, 2002, Stone, et al, 2003. Figure 3 is a snapshot of an equilibrium configuration of a perfluoropolyether ammonium carboxylate (CF 3 (OCF 2 CF(CF 3 )) 3 OCF 2 COO -NH 4 + ) (PFPE-COO-NH 4 + ) surfactant at the C|W interface (da Rocha, et al, 2002) obtained by MD computer simulations.…”
Section: Microscopic Information On Monolayers At the Co 2 -Water Intmentioning
confidence: 86%
“…[152] Further MD simulation studies focused on the formationo fr eversem icelles, on the structure-property relationship for different surfactant molecules, [153] and on the CO 2 -philic behavior of the surfactant tails. [154] The structuralf eatures of surfactants at the water-CO 2 interface were investigated by Rossky's group, who showedt hat CO 2 can solvate the fluorinated tails as wellasthe hydrocarbon tails, leading to an ew orientationalo rdering that allows increasedw ater accessibility of the hydrophobic part. [155,156] Aj oint experimental and computational study by Berkovitz et al characterized am icroemulsion in as ystem containing a fluorinated surfactant, water and scCO 2 .…”
Section: Fluorinated Compoundsmentioning
confidence: 99%